PENGARUH MODEL PEMBELAJARAN INDEX CARD MATCH TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD MUHAMMADIYAH MIMBAR - Wd. Lulu Fitria R. Mursalim; Andi Mulawakkan Firdaus; Sirajuddin (STKIP Subang, 2026)
This study aims to determine the effect of implementing the Index Card Match learning model on the interest and mathematics learning outcomes of fourth-grade students at SD Muhammadiyah Mimbar. This study uses a quantitative approach with a pre-experimental research type and a one-group pretest-posttest design. The research subjects were fourth-grade students at SD Muhammadiyah Mimbar, totaling 24 students. Data collection techniques used a learning interest questionnaire and a mathematics learning outcome test. Data analysis employed the Shapiro-Wilk normality test and the paired sample t-test. The results of the study indicate that there was an increase in students' interest in learning after implementing the Index Card Match model, with the average learning interest score increasing from 58.25 to 69.21. In addition, students' mathematics learning outcomes also improved, as shown by the average pretest score of 67.50 and posttest score of 80.21. The paired t-test results showed a significance value of 0.000 (p < 0.05), which means that there is a significant effect of applying the Index Card Match model on students' interest and learning outcomes in mathematics. Therefore, it can be concluded that the Index Card Match learning model has a significant impact on improving the interest and learning outcomes in mathematics of fourth-grade students at SD Muhammadiyah Mimbar. This model is effective because it is able to create an active, interactive, and enjoyable learning environment.